Disseminating education to solid organ transplant recipients to promote engagement in physical activity - Sunita Mathur; Neha Dewan; Tania Janaudis-Ferreira; Patrick Antonio; Holly Surins; Robin Deliva; Catherine Patterson; Stephanie So (Elsevier, 2022)
Objective: To evaluate the dissemination of education through a workshop to promote engagement in physical activity (PA) among solid organ transplant (SOT) recipients. Methods: The in-person workshop consisted of expert-led lectures on topics related to physical activity (day 1) and sports and fitness training with volunteer coaches (day 2). There were separate streams for children/adolescents and adults. RE-AIM (Reach, Efficacy, Adoption, Implementation, and Maintenance) framework was used to evaluate the impact of the workshop. Presenters and participants completed evaluations of the workshop using a 5-point Likert scale. A subgroup of adults completed a self-reported PA questionnaire at baseline and 4-weeks after the workshop. Results: 103 individuals (71 SOT recipients, 32 caregivers) attended the workshop (ages 4 to 71+ years). Sessions were highly rated (median = 5) for both quality and content on both days. There was no significant change (p = 0.16) in PA. However, 56% of SOT recipients reported changing their level of PA. Conclusion: An educational-workshop with hands-on training was an efficient and well-received method for disseminating awareness about the benefits of PA in SOT recipients. Innovation: Dissemination of evidence-based knowledge through a novel educational-workshop in a real-world setting has the potential to inform the decisions about PA behavior among SOT recipients.